MODEL KESIAPSIAGAAN KELUARGA TERHADAP ANCAMAN BAHAYA BENCANA GEMPA BUMI DESA CONDONGCATUR, KAPANEWON DEPOK, KABUPATEN SLEMAN, D.I. YOGYAKARTA - Puspitasari, Lisa; Prastistho, Bambang; Prasetya, Johan Danu (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2023)
This study aims to find out the model of family preparedness, describe infrastructure facilities foe earthquake threat and assess factors that are the level of preparedness of the people of Condongcatur village against the threat of earthquake disasters. The study used quantitative methods, as well as sampling using purposive sampling techniques with family preparedness scale measurement tools, factors that affect family preparedness levels and observation sheets of facilities and infrastructure. The study subjects were people living in the village of Condongcatur and their analytical techniques using multiple regression analysis and using the help of the SPSS 23.00 for windowa computer program. The results of multiple regression analysis obtained knowledge variables about earthquakes with a calculated value 4,295, variable emergency response plan value tcalculate 2,416, variabel disaster warning system value tcalculated 3,065 and variable of resource mobility value tcalculated 7,280 with significance value 0,000 < 0,05 which means it can be concuded that preparedness in the village of Condongcatur against the threat of earthquakes in the category of ready and factores that affect preparedness in the village of Condongcatur against the threat of earthquake disaster in the category of very ready, as well as observation of facilities and infrastructure for the threat of earthquake disaster in the village of Condongcatur in the high category. Advice for researchers is expected to develop supporting factors that affect family preparedness in the village of Condongcatur against the threat of earthquake hazards.